Impact of Annually Variable Dust Activity on the Recession of the Martian South Polar Seasonal Cap - Zhibin Li; Jianjun Liu; Renhao Tian; Zhaopeng Chen; Qing Zhang; Jingjing Zhang; Wei Yan; Qiang Fu; Shaoran Liu; Nannan Ma (The Astronomical Journal)
Suspended dust is a vital component of Martian climatic system and its temporal-spatial variation can influence the recession of the South Polar Seasonal Cap (SPSC). However, dust activity varies across different stages and years, affecting the SPSC recession process differently. Continuous observations of SPSC/South Polar Residual Cap (SPRC) across several Martian years, alongside segmented analyses of annual dust activity, will provide new insights into the climate conditions of Martian south polar region. Here, we performed a combined analysis on the extents of SPSC from MY28-MY31 and MY36, together with the concurrent Martian atmospheric optical thickness, to assess the influence of dust activity at various recession time steps. Results show that dust activity peaks in both spring and summer can impact the SPSC/SPRC recession. The recession process is accelerated if the dust activity peak occurs earlier. If the timing of the peak dust activity is identical, the intensity of the dust activity influences the recession. Specific regions, such as the “Cryptic Region” and the Mountains of Mitchel, respond uniquely to dust activity. Higher dust intensity slows the recession of the Cryptic Region, while the SPSC in the Mountains of Mitchel area shows variability in recession timing based on local dust activity intensity. This research provides observational constraints that enhance our understanding of Martian atmospheric circulation and can potentially aid the future development of polar dust activity models.